Study of essential oil in Monarda fistulosa L. (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The biomorphological and вiochemical features of Monarda fistulosa L. cultivated in Kherson area are given in . The contents of essential oil in plant is determined. Its localization togerter with oil glandulae size on leaves is studied. The comparative characteristics of the essential oil content for cv. Premyera and for other forms of Monarda fistulosa is discussed. Circadian dynamics of oil accumulation during different development phases is studied. It is established, that there are 20 components in the essential oil with the main component Thymol.
Keywords: Monarda fіstulosa L., Kherson area, phase of development, essential oil, glandulae, composition.